Recommendations for an update of the 2010 European regulatory guideline on clinical investigation of medicinal products used in the treatment of osteoarthritis and reflections about related clinically relevant outcomes: expert consensus statement. Issue 12 (December 2015) - Reginster, J.-Y.; Reiter-Niesert, S.; Bruyère, O.; Berenbaum, F.; Brandi, M.-L.; Branco, J.; Devogelaer, J.-P.; Herrero-Beaumont, G.; Kanis, J.; Maggi, S.; Maheu, E.; Richette, P.; et al.
Summary: Objective: The European Society on Clinical and Economic aspects of Osteoporosis and Osteoarthritis (ESCEO) organised a working group to evaluate the need for updating the current European guideline on clinical investigation of drugs used in the treatment of osteoarthritis (OA). Design: Areas of potential attention were identified and the need for modifications, update or clarification was examined. Proposals were then developed based on literature reviews and through a consensus process. Results: It was agreed that the current guideline overall still reflects the current knowledge in OA, although two possible modifications were identified. The first relates to the number and timing of measurements required as primary endpoints during clinical trials of symptom-relieving drugs, either drugs with rapid onset of action or slow acting drugs. The suggested modifications are intended to take into consideration the time related clinical need and expected time response to these drugs – i.e., a more early effect for the first category in addition to the maintenance of effect, a more continuous benefit over the long-term for the latter – in the timing of assessments. Secondly, values above which a benefit over placebo should be considered clinically relevant were considered. Based on literature reviews, the most consensual values were determined for primary endpoints of both symptom-relieving drugs (i.e., pain intensity on a visual analogue scale (VAS)) and disease-modifying drugs (i.e., radiographic joint-space narrowing). Conclusions: This working document might be considered by the European regulatory authorities in a future update of the guideline for the registration of drugs in OA.